Preformulation Studies and Pseudo-Ternary Phase Diagram Development for Dolutegravir Sodium: A Foundational Step toward SMEDDS Design - Hiremath, Jayadev; Naveen, Nimbagal Raghavendra; Goudanavar, Prakash; Meravanige, Girish; Fattepur, Santosh; Almuqbil, Rashed M.; Aldhubiab, Bandar; Nagaraja, Sreeharsha (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Dolutegravir Sodium (DTG) is a poorly soluble antiretroviral drug that will find it difficult to achieve oral bioavailability. Preformulation and screening of excipients are mandatory as a stepping stone in formulation development. Objectives: To conduct comprehensive preformulation studies and build pseudo-ternary phase diagrams for DTG with a view to informing future development of a stable SMEDDS formulation. Materials and Methods: UV spectrophotometry was used to establish the maxima of absorption and to construct a standard calibration curve for DTG. Solubility studies were performed using various oils and surface-active agents. The efficiency of emulsification was used to screen the surfactants, while compatibility was established through the use of FTIR spectroscopy. Pseudo-ternary diagrams identified microemulsion regions with Capmul MCM C8 oil and Kolliphor EL/propylene glycol Smix. Results: Enhanced solubility of DTG has been observed in Capmul MCM C8. Kolliphor EL and propylene glycol were chosen to be the surfactant and co-surfactant, respectively, for their emulsification capacity and high transmittance (>94%). FTIR established no meaningful incompatibilities between DTG and chosen excipients. Of Smix ratios examined, 3:1 (Kolliphor EL:PG) showed the largest microemulsion area in pseudo-ternary phase diagrams. Conclusion: The study offers a clear preformulation platform for DTG, determining important excipients and a best-fit Smix ratio for microemulsion development. Ternary phase diagrams were constructed to confirm the choice of ingredients for a possible SMEDDS. Subsequent research will construct on this basis to develop and assess a DTG-loaded SMEDDS for enhanced oral bioavailability.
Keywords: Dolutegravir sodium; Ternary Phase Diagram; SMEDDS; Lipid Based Systems